Scalable and energy-efficient synthesis of CoxP for overall water splitting in alkaline media by high energy ball milling. Issue 4 (22nd January 2020) - Xue, Hongyao; Zhang, Haiqin; Fricke, Sebastian; Lüther, Marco; Yang, Zijiang; Meng, Alan; Bremser, Wolfgang; Li, Zhenjiang
Abstract : Earth-abundant catalysts based on transition metal phosphides (TMPs) such as Co x P have recently gained a lot of attention in the field of electrocatalysis and are usually acquired by chemical synthesis. Abstract : Earth-abundant catalysts based on transition metal phosphides (TMPs) such as Co x P have recently gained a lot of attention in the field of electrocatalysis and are usually acquired by chemical synthesis. Herein, we present a mechanical synthesis method (high energy ball milling) for preparing a bifunctional Co x P electrocatalyst at room temperature (25 °C) using black phosphorus (BP) and cobalt(iii ) oxide (Co2 O3 ) as raw materials. This safe, energy-efficient and scalable method yields a durable catalyst material, which achieves a current density of 10 mA cm −2 at low overpotentials of 69 mV and 266 mV in 1 M KOH for the HER and OER, respectively, as well as low Tafel-slopes of 50.6 mV dec −1 and 62.1 mV dec −1 . When the Co x P electrocatalyst was employed for overall water splitting, current densities of 10 mA cm −2 and 100 mA cm −2 were achieved at 1.59 V and 1.97 V surpassing those of the state-of-the-art Pt/C‖RuO2 setup. Moreover, the outlined synthesis route could potentially be applied to other transition metals allowing for the facile production of other catalysts.